The humanities are not our patient. Issue 3 (July 2021) - Thanem, Torkild; Wallenberg, Louise
When inviting contributions to a special issue of this journal titled 'Management Learning and the Unsettled Humanities' the guest editors did not simply encourage contributors to explore possibilities 'for reciprocal integration' between the two realms. Stressing that 'the humanities . . . [are] facing a complex crisis on their own', they stated that 'the humanities . . . need to be enriched, nuanced, and critiqued through . . . the ideas and perspectives of organisational research'. While we may agree that all is not well in the humanities and share their scepticism towards 'just prescribing the value of the humanities to ameliorate the ills of management education', we are less confident that the humanities need management learning as much as we need them. As long as learning and scholarship in management and organisation studies continues to suffer from too much management, we doubt that 'management education [may help] . . . unsettl[e] . . . the human within the . . . humanistic . . . disciplines'. Rather, students of management and organisation still have plenty to learn from the humanities, not least from its rich portrayal of human lives. It is on this basis we draw the conclusion that the humanities are not our patient.